2015
DOI: 10.1038/tpj.2015.55
|View full text |Cite
|
Sign up to set email alerts
|

Variability in hepatic expression of organic anion transporter 7/SLC22A9, a novel pravastatin uptake transporter: impact of genetic and regulatory factors

Abstract: Human organic anion transporter 7 (OAT7, SLC22A9) is a hepatic transport protein poorly characterized so far. We therefore sought to identify novel OAT7 substrates and factors contributing to variable hepatic OAT7 expression. Using OAT7-expressing cells, pravastatin was identified as a substrate. Hepatic SLC22A9/OAT7 mRNA and protein expression varied 28-fold and 15-fold, respectively, in 126 Caucasian liver samples. Twenty-four variants in SLC22A9 were genotyped, including three rare missense variants (rs3772… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 45 publications
2
39
0
Order By: Relevance
“…(cell structure and proliferation; IRS: 11.11%) and BANP (migration and invasiveness; IRS: 10.73%) were all previously reported in the literature (42)(43)(44)(45)(46)(47)(48)(49)(50). This observation may suggest that highly immunogenic neoantigens are 'tolerated' preferentially if the cells gain a compensatory survival advantage from the mutation by switching off a tumor-suppressive pathway, supporting their role of propelling MSI tumor evolution ( Fig.…”
Section: Immunoselection During Msi Carcinogenesissupporting
confidence: 70%
“…(cell structure and proliferation; IRS: 11.11%) and BANP (migration and invasiveness; IRS: 10.73%) were all previously reported in the literature (42)(43)(44)(45)(46)(47)(48)(49)(50). This observation may suggest that highly immunogenic neoantigens are 'tolerated' preferentially if the cells gain a compensatory survival advantage from the mutation by switching off a tumor-suppressive pathway, supporting their role of propelling MSI tumor evolution ( Fig.…”
Section: Immunoselection During Msi Carcinogenesissupporting
confidence: 70%
“…We found that urate transport mediated by OAT7 is inhibited by the uricosuric drugs benzbromarone and tranilast, which inhibit multiple other urate transporters [50]. Three uncommon missense variants that influence the ability of OAT7 to transport pravastatin by either causing the protein to be retained intracellularly or reducing protein levels at the plasma membrane have been reported [51], all at a frequency < 1% in East Asian. HNF4 α plays a key role in the transactivation of the SLC22A9 promoter [51], an interesting observation given that HNF4 α is also required for expression of the gene encoding the urate transportosome-stabilizing molecule PDZK1 in the liver [11], and is implicated in control of serum urate levels via the MAFTRR locus [12].…”
Section: Discussionmentioning
confidence: 99%
“…NGS was conducted at the Center for Genomics and Transcriptomics (CeGaT GmbH, Tübingen, Germany) as previously described. 39 Details are provided in the supplementary methods.…”
Section: Methodsmentioning
confidence: 99%